Management of Acute Intracerebral Hemorrhage - Vinall, Phil (MD Conference Express, 2010)
This article discusses the prevention, management, and processing of intracerebral hemorrhage (ICH), as well as key clinical trials concerning the surgical management of ICH. This article also reviews the tools and procedures for recovery and prevention of ICH recurrence.